Premolis semirufa (Walker, 1856) envenomation, disease affecting rubber tappers of the Amazon: searching for caterpillar-bristles toxic components. - Isadora Maria Villas-Boas; Rute Maria Gonçalves-; Giselle Pidde-Queiroz; Suely Lucia Muro Rais Assaf; Fernanda C V Portaro; Osvaldo A Sant'Anna; Carmen W van den Berg; Denise V Tambourgi (Public Library of Science (PLoS), 2012)
BACKGROUND: The caterpillar of the moth Premolis semirufa (Lepidoptera: Arctiidae), commonly named Pararama, is endemic of the Amazon basin. Accidental contact with these caterpillar bristles causes local symptoms such as intense heat, pain, edema and itching which last for three to seven days; however, after multiples contacts, it may induce joint-space narrowing and bone alteration, as well as degeneration of the articular cartilage and immobilization of the affected joints. Specific treatment for this disease does not exist, but corticosteroids are frequently administered. Despite of the public health hazard of Premolis semirufa caterpillar poisoning, little is known about the nature of the toxic components involved in the induction of the pathology. METHODOLOGY/PRINCIPAL FINDINGS: Here we have investigated the biological and immunochemical characteristics of the caterpillar's bristles components. Analysis of the bristles extract in in vitro assays revealed the presence of proteolytic and hyaluronidase activities but no phospholipase A(2) activity. In vivo, it was observed that the bristles extract is not lethal but can induce an intense inflammatory process, characterized by the presence of neutrophils in the paw tissues of injected mice. Furthermore, the bristles components stimulated an intense and specific antibody response but autoantibodies such as anti-DNA or anti-collagen type II were not detected. CONCLUSION: The results suggest that Premolis semirufa caterpillar bristles secretion contains a mixture of different enzymes that may act together in the generation and development of the clinical manifestations of the Pararama envenomation. Moreover, the high immunogenicity of the caterpillar bristles components, as shown by the generation of high antibody titers, may also contribute to the induction and establishment of the inflammatory disease.